Analysis of Land Use Developments Along the LRT Line (Case Study: Polresta, Jakabaring and DJKA Station’s) - Putri, Erliza Miranda; Herwangi, Yori (ASTONJADRO, 2023)
Transportation has become a basic need that plays an important role in people’s lives. To reach a place, a high level of accessibility is required. A high level of accessibility will affect the number of people coming to an area. Many people will affect the number of activities that require land. Therefore, this study aims to analyze land use trends that occurred in the time period before and after the South Sumatra LRT. LRT or Light Rail Transit is a type of public transportation in the form of light rail operating in urban areas. LRT is the first light rail transportation in Indonesia right in Palembang City. Therefore, it is interesting to see its relation to land change along the LRT route. This research was conducted at three stations which were case studies, namely Polresta, Jakabaring and DJKA stations. This station was chosen because it is in Jakabaring. Jakabaring was chosen as the research area because it is a sub-district which is located on the border with other regencies but is still passed by the LRT. This research is a qualitative research using the overlay before-after analysis method through spatial data. This research uses the help of Archgis software, through Intersect tools and multiple ring buffers. The results of the analysis are then used as data for further analysis using a pivot table in excel. The results of this analysis prove that there is a tendency for changes in land use within a certain radius. The trend is in the form of changes in land from swamps or paddy fields to deserted, trade and services as well as offices.